The Last Step in Cocaine Biosynthesis Is Catalyzed by a BAHD Acyltransferase. Issue 1 (18th November 2014) - Schmidt, Gregor Wolfgang; Jirschitzka, Jan; Porta, Tiffany; Reichelt, Michael; Luck, Katrin; Torre, José Carlos Pardo; Dolke, Franziska; Varesio, Emmanuel; Hopfgartner, Gérard; Gershenzon, Jonathan; D'Auria, John Charles
Abstract : The terminal step in cocaine biosynthesis is catalyzed by an acyltransferase that utilizes benzoyl-CoA and methylecgonine as substrates and is localized to the spongy mesophyll . Abstract: The esterification of methylecgonine (2-carbomethoxy-3β-tropine) with benzoic acid is the final step in the biosynthetic pathway leading to the production of cocaine in Erythoxylum coca . Here we report the identification of a member of the BAHD family of plant acyltransferases as cocaine synthase. The enzyme is capable of producing both cocaine and cinnamoylcocaine via the activated benzoyl- or cinnamoyl-Coenzyme A thioesters, respectively. Cocaine synthase activity is highest in young developing leaves, especially in the palisade parenchyma and spongy mesophyll. These data correlate well with the tissue distribution pattern of cocaine as visualized with antibodies. Matrix-assisted laser-desorption ionization mass spectral imaging revealed that cocaine and cinnamoylcocaine are differently distributed on the upper versus lower leaf surfaces. Our findings provide further evidence that tropane alkaloid biosynthesis in the Erythroxylaceae occurs in the above-ground portions of the plant in contrast with the Solanaceae, in which tropane alkaloid biosynthesis occurs in the roots.